Allocation Rules for Network Games - Matthew O. Jackson (Fondazione Eni Enrico Mattei (FEEM), 2003)
Previous allocation rules for network games, such as the Myerson Value, implicitly or explicitly take the network structure as fixed. In many situations, however, the network structure can be altered by players. This means that the value of alternative network structures (not just sub-networks) can and should influence the allocation of value among players on any given network structure. I present a family of allocation rules that incorporate information about alternative network structures when allocating value.
Keywords: A14; C71; C72; 330; Networks; Network Games; Allocation Rules; Cooperative Games; Netzwerk; Kooperatives Spiel; Allokation; Theorie